Factors affecting menopause in Nepalese women - Paudel, Puja; Bhandary, Shital; Byanju, Jayandra (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Menopause is a physiological event that indicates the end of reproductive period in woman’s life. It has many health issues and morbidity. There are multiple factors that influence age of onset of menopause and we aim to find these associated factors.Methods: The 2011 ‘Nepal demographic and health survey’ data was used in this study. Logistic regression was used to find the association between the dependent and independent variables using bi-variate and multi-variate analysis.Results: The bivariate analysis showed the association of age, wealth index, education, marital status, employment, use of oral contraceptives and smoking with menopause. The multivariate analysis showed the independent association of age, education, employment and oral contraceptives.Conclusions: The employment, marital status and use of oral contraceptives were found to be independently associated with the age of onset of menopause on multivariate analysis.